Breaking the English Routine: An Argument for Polylingual Discourse in U.S. Higher Education - Taylor, Z.W. (Journal of Praxis in Higher Education, 2021)
Extant research has suggested United States (U.S.) higher education is more accessible and equitable toward Whites than toward English-language learners, international students, and students of color (Bernal, 2002; Lee & Rice, 2007; Lippi-Green, 2012; Yeh & Inose, 2003). In this argumentative essay, I insist these issues of access and equity are partially owed to the Anglocentric, highly routinized, and luddite nature of U.S. higher education communication, policy, and practice. Moreover, I forward the notion that predominantly English institutions (PEIs) should explore performing non-routine, highly technological work in order to value the linguistic capital (Yosso, 2005) brought to the institution by students with diverse language knowledge in order to truly serve students from minoritized language populations. Implications for linguistic equity and the practicality of polylingual institutional support is addressed.